2021
DOI: 10.3332/ecancer.2021.1307
|View full text |Cite
|
Sign up to set email alerts
|

African American participation in cancer clinical trials

Abstract: Background: According to the Food and Drug Administration, African Americans (AAs) have been habitually underrepresented in cancer clinical trials (CCTs). This under-enrolment has contributed to cancer disparities despite the implementation of policies to improve AA accrual. This systematic review aimed to determine (1) Why AAs are participating in CCT at lower rates compared to other ethnic/racial groups and (2) Are there any tools that have definitively improved AA participation or addressed the barriers ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
(135 reference statements)
0
8
2
2
Order By: Relevance
“…A study that looked at cancer health literacy among African Americans, Whites, and Hispanics backed with similar findings. On a cancer health literacy test, African American participants scored much lower than white participants [28]. The relatively lower level of health literacy among African Americans could lead to problems in understanding the informed consent process in biomedical research, a common obstacle to African American involvement in CCT [27,29].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A study that looked at cancer health literacy among African Americans, Whites, and Hispanics backed with similar findings. On a cancer health literacy test, African American participants scored much lower than white participants [28]. The relatively lower level of health literacy among African Americans could lead to problems in understanding the informed consent process in biomedical research, a common obstacle to African American involvement in CCT [27,29].…”
Section: Discussionmentioning
confidence: 97%
“…The relatively lower level of health literacy among African Americans could lead to problems in understanding the informed consent process in biomedical research, a common obstacle to African American involvement in CCT [27,29]. Another qualitative study interviewing African American cancer survivors at a safety-net hospital identified that a lack of understanding of cancer clinical trials was one of the major barriers of participation in cancer trials [28,30]. The study reported that many survivors were confused and even could not be differentiated between a cancer clinical trial and treatment of cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcoidosis occurs three times more commonly in African Americans and presents with disproportionate severity in patients of a lower socioeconomic status (SES) (40,42,45,103,104), yet most trial populations thus far have not been reflective of this racial prevalence of disease (105,106). Several studies show that African Americans are less likely to both qualify for and to participate in clinical trials due to several reasons such as mistrust in the system, lack of interest in clinical trials, fear and stigma associated with participation, and a perception that they may not be compliant with trial protocols (107)(108)(109)(110). Several strategies that have improved clinical trial participation for minorities and the underserved in other diseases may also be deployed in sarcoidosis (108,111,112).…”
Section: Challenges Affecting Drug Trials and Drug Development In Sar...mentioning
confidence: 99%
“…9,16,17 Inclusion of diverse study participants varies by institution and cancer type, 3,9 but participation of people who are Black and/or Hispanic/Latinx has remained consistently low or decreased. 3,18 Under-representation of racial and ethnic minority populations may be more extreme, because < 33% of cancer trials report race and ethnicity data. 3,9 The Food and Drug Administration's (FDA) Oncology Center of Excellence has encouraged trial sponsors to set enrollment targets that reflect epidemiologic characteristics of the disease.…”
Section: Introductionmentioning
confidence: 99%